CONTRIBUTION OF AGRICULTURAL SOCIETIES TO STUD MATTER DEVELOPMENT IN CATTLE BREEDING ON UKRAINIAN LANDS AS PART OF THE RUSSIAN EMPIRE (the beginning of the 20th century) - CHALAVAN, Victor; PYLYPENKO, Liliia (EAST EUROPEAN HISTORICAL BULLETIN, 2025)
The purpose of the research is to identify the most significant achievements and initiatives of agricultural societies of Ukraine under Russian rule in the direction of developing breeding in cattle breeding in 1907 – 1915 (although the chronology of the study partially goes beyond this framework). The methods of the research are based on the principles of objectivity, systematics, historicism; historical genetic, historical systemic, historical typological methods, as well as there have been applied the methods of scientific criticism of historical sources. The scientific novelty of the study consists in the comprehensive analysis of the agricultural societies contribution of the specified period to cattle breeding development. Conclusions. It has been determined that the issues on the improving livestock breeding in Ukrainian lands at the beginning of the 20th century were dealt with by the majority of agricultural societies that had branch departments. Hence, the Imperial Agricultural Society of Southern Russia (Odesa) focused on the development of sheep and horse breeding. The Poltava Society of Agriculture and Agricultural Industry made a significant contribution to the development of sheep and pig breeding. Yelyzavethradske Agricultural Society developed measures to improve the care of cattle and established a horse breeding committee. However, as it turned out, the greatest contribution to the development of breeding in cattle breeding in the studied period was made by Kharkiv, Kyiv and Podilsk Agricultural Societies. The first of them is the initiative to introduce a cattle stud book, the development of which began in 1907. By the end of 1913 on the analogy with Kharkiv stud books were introduced in other regions of the empire. The merit of the Livestock Department of Kharkiv Agricultural Society was the organization of the first control unions for fattening cattle in Ukraine, which began to function in 1910 – 1911. In 1913, the so-called “Mixed Russian-Swiss Committee for the Purchase of Swiss Pedigree Cattle” was established at the Livestock Department of Kyiv Agricultural Society, access to which was open to all agricultural societies, zemstvos and individual farmers of the Russian Empire. The Committee's activities were aimed at eliminating intermediaries in the livestock trade. In 1915 the Podilsk Union of Cattle Breeders at Podilsk Agricultural Society included more than 100 purebred cattle factories in Podilsk, Kyiv, and Volyn hubernias. It is proven that these activities of agricultural societies contributed to the search of rational methods of animal husbandry, the acquisition of breeding material and the profitable sale of livestock products. The agricultural societies made an important contribution to the formation and development of breeding in Ukrainian cattle breeding at the beginning of the 20th century, in particular, in the development of animal breeding selection programs, effective methods and technologies for the reproduction of valuable breeding resources, practical recommendations for the application of scientific and technical achievements in production, etc. Key words: livestock, cattle breeding, breeding business, agricultural societies, cattle breeding book, control unions for cattle fattening.